Leaf fatty acid remodeling in the salt-excreting halophytic grass Spartina patens along a salinity gradient - Duarte, Bernardo (2020)
Spartina patens is a highly dispersed halophytic grass invader in Mediterranean marshes. It is also characterized by having a high degree of resistance to salinity, one of the main drivers of plant zonation in salt marshes. Nevertheless, the physiological basis behind the extreme resistance of S. patens requires more detailed studies. In the present work, we aimed to study how membrane fatty acid remodeling could contribute to the resistance of this plant to salt. Spartina patens individuals exposed to increasing levels of salinity and its leaf fatty acid profile under lipid peroxidation products evaluated under all tested concentrations. A significant increase in the relative amounts of the saturated fatty acids (SFA) was observed, namely palmitic acid (C16:0), essential for PS II functioning, and stearic (C18:0) acid. The chloroplastidial trans-hexadecenoic acid (C16:1t) as well as the polyunsaturated linoleic (C18:2) and linolenic (C18:3) acids showed significant decreases in all the salt treatments. These changes led to a reduction in the double bond index in salt-treated plants which reflects reduction of the fluidity of the chloroplast membranes, which could contribute to maintain the membrane impermeable to the toxic exogenous Na. Despite the decrease observed in the total fatty acid contents in plants exposed to high salt concentrations the amounts of lipid peroxidation products decreased highlighting the resistance of this species towards toxic exogenous salt concentrations. Membrane fatty acid remodeling could represent an efficient mechanism to maintain the photosynthetic machinery of S. patens highly efficient under salt stress.